DARI SAMPAH JADI RUPIAH: PEMBERDAYAAN PKK BENDOSARI MELALUI PEMBUATAN MODEL BANK SAMPAH ORGANIK BERBASIS BIOPORI UNTUK PENINGKATAN EKONOMI DAN LINGKUNGAN - Puspita, Maria Entina; Krisnianda, Elen; Agnestiana, Maria Rutverra; Suyatno, Anggun Maulinda; Hidayat, Fajar; Fadilla, Annisa Nurul (STIE Pelita Nusantara, 2025)
This community service program aims to empower the women of PKK RT 005 Dusun Bendosari through household waste management using the Bank Sampah Unit (BSU) model and Lubang Resapan Biopori (LRB). The methods applied include socialization, training, hands-on practice, and mentoring with a project-based learning approach. The results indicate that participants are able to independently separate organic and inorganic waste, process organic waste into compost through biopores, and use the compost to support the Nutrition Garden, which produces vegetables such as mustard greens, water spinach, and spinach. Furthermore, through BSU, the community gains economic benefits from the sale of recyclable inorganic waste. This program not only enhances environmental awareness and community cleanliness but also increases household income while reducing expenses through the consumption of vegetables from the Nutrition Garden. Thus, the activity creates a dual impact by improving household economic welfare and promoting sustainable environmental preservation